Requirements Discovery for a Production Management Software - Nordkvist, Kim (My University, 2013)
Due to the expanding Condition Based Maintenance (CBM) business at Wärtsilä Oyj a software tool was needed to ease and secure the maintainability of the installed base, delivery requirements, contract and invoicing information. Another aim with this tool was to achieve a degree of predictability of the CBM services by having information available about forthcoming requests for CBM systems and services. As a result, a tool with up-to-date information would serve many stakeholders with all available CBM related information but also remarkably reduce the work load needed to maintain this information manually. The objective of this thesis was to gather and document the requirements. For the requirements discovery a use case based requirements elicitation technique was selected. It was selected because use cases can be documented in a structured way and also because they are a good tool to communicate the behavioural functions of a system between users and software developers. Requirements were also discovered by studying documents, tools, and process, but also by arranging interviews and having discussions with the stakeholders. All the requirements were documented in a Software Requirements Specification using a template from IEEE Std 830-1998. The result of this thesis is a Software Requirements Specification that defines the requirements for this new tool. It was observed that even though it takes only a few minutes to learn read use cases, learning to write good use cases requires much more effort. In addition, the use cases are an important input when making the functional design specification, but they also serve as a base for designing the test cases that the new software will have to meet. Finally, the most important lesson learned was the importance of specifying software requirements that cannot be ignored.
Keywords: user requirements; requirements discovery; use cases; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|